West African Migrations Transnational and Global Pathways in a New Century - Okome, M.; Okome, M. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
Drawing on the interdisciplinary research projects of scholars from various social science and humanities disciplines, this book explores how African migration to Western countries after the neo-liberal economic reforms of the 1980s transformed West African states and their new transnational populations in Western countries.